The Influence Of Marketing Communications On Loyalty Through Satisfaction - Ahmad Fadli; Fiqrida Amalia; Emma Novirsari; Ratih Amelia; Muhammad Fathoni (Journal of Business and Management Review, 2021)
The main objective of this study is to determine the role of satisfaction in mediating marketing communications on visitor loyalty in Lake Toba. The target population and sample in this study were the visitors to Lake Toba who were selected by accidental sampling as many as 125 people. Path analysis in this study was chosen to see the direct and indirect role of satisfaction in mediating marketing communications on loyalty. The results of study 1) direct marketing communication has a positive and significant effect on visitor satisfaction at Lake Toba, 2) directly marketing communication does not affect visitor loyalty in Lake Toba. 3) Satisfaction directly has a positive and significant effect on visitor satisfaction at Lake Toba. 4) indirectly, satisfaction has a role in mediating marketing communication on visitor loyalty in Lake Toba